AKIBAT HUKUM PEMBELIAN SAHAM PERUSAHAAN BUKAN PENANAMAN MODAL ASING OLEH WARGA NEGARA ASING ATAU BADAN HUKUM ASING - Ucok Yoantha; Budiman Ginting; Suhaidi Suhaidi,; Mahmul Siregar (Universitas Sumatera Utara, 2015)
ABSTRACT The presence of foreign capital investment in Indonesia is very important and strategic in supporting the implementation of national development. Indonesia's national development requires enormous funding to be able to support the economic growth rate is expected. Funding needs are not only can be obtained from domestic funding sources, but also from abroad. It causes foreign investment becoming one of foreign funding sources that support the strategic national development, especially in the development of the real sector which in turn is expected to have an impact on the opening of the field work widely. The results showed that foreign nationals or foreign corporations can make purchases in the acquisition of shares in the company after the acquisition but not PMA, the PMA company is not required to form a limited liability company may be acquired and even then there will be restrictions on ownership of foreign citizens or foreign legal entity the company instead of the PMA and the PMA company is not turned into a PMA company, whereas for the control and supervision carried out gradually from the center by BKPM up to the provincial and district / city. Keyword : legal consequences, share purchase, a foreign legal entity